Design of novel cobalt-based perovskite derivatives using sulfurization as active material of energy storage devices. (25th November 2022) - Cheng, Tsai-Mu; Chu, Hsiu-Yi; Cao, Yu-Cheng; Kubendhiran, Subbiramaniyan; Lee, Pin-Yan; Yougbaré, Sibidou; Lin, Lu-Yin; Wu, Yung-Fu
Abstract: Metal organic framework (MOF) derivatives have attracted much attention as efficient active material of energy storage device, due to large surface area, excellent pore structure and abundant redox states. Previously ammonia fluoride is used to control morphology of zeolitic imidazolate framework 67 (ZIF-67) and supply NH4 + and F − to enhance charge transfer. More treatments are worthy to apply for improving energy storage ability of this ZIF-67 derivative. In this study, sulfurized ammonium-decorated cobalt fluoride (S-NH4 -CoF) is firstly synthesized using ZIF-67 derivative and sulfur powder in the one-step annealing process at different temperatures as active material. The optimized S-NH4 -CoF electrode prepared at 400 °C shows specific capacitance (CF ) of 462.1 F g −1 at 20 mV s −1, due to round particle-assembled sphere morphology with high surface area and large pore volume, and suitable ratio of cobalt fluoride and cobalt sulfide. The symmetric energy storage device composed of optimized S-NH4 -CoF electrodes shows maximum energy density of 30.47 Wh kg −1 at 800 W kg −1 . The CF retention of 85% and Coulombic efficiency higher than 97% are obtained after 20, 000 charge/discharge times. This study supplies important information about sulfurization on MOF derivatives. Other parameters like sulfurization precursor and duration are worthy to discuss for enhancing energy storage ability of S-NH4 -CoF. Graphical abstract: Unlabelled Image Highlights: Sulfurized ammonium-decorated cobalt fluoride (S-NH4 -CoF) is firstly synthesized. The ZIF-67 derivative and sulfur powder are used as precursor for one-step annealing. Optimal S-NH4 -CoF electrode shows specific capacitance (CF ) of 462.1 F g −1 at 20 mV s −1 . Device with S-NH4 -CoF electrode shows max. energy density of 30.47 Wh kg −1 at 800 W kg −1 . The CF retention of 85 % and Coulombic efficiency of 97 % are got after 20, 000 cycles.